Milton and the Puritan dilemma, 1641-1660 - Barker, Arthur Edward, 1911- (Studies and texts (University of Toronto. Department of English), 1976)
Professor Barker interprets Milton's development in the light of his personal problems and of the changing climate of opinion among his revolutionary associates.